Akt downstream of NFκB, MAPKs and IRF3 pathway involved in macrophage activation induced by Astragalus polysaccharide RAP. (December 2017) - Li, Zhi-Peng; Li, Li-Feng; Zhang, Quan-Wei; Wei, Wei; Liu, Hong-Bing; Bao, Wan-Rong; Ma, Dik-Lung; Leung, Chung-Hang; Bian, Zhao-Xiang; Lu, Ai-Ping; Han, Quan-Bin
Highlights: IRF3 pathway played an activation role in RAP induced macrophage. Akt played an activation role in RAP induced macrophage. Akt exerted effect downstream of MyD88 dependent NFκB and MAPKs pathway. Akt exerted effect downstream of MyD88 independent IRF3 pathway. Abstract: Polysaccharides are considered the main active ingredient for the immune-enhancing effect of Radix Astragali, which is popularly used as medicinal food supplementary. The signal pathways involved in immune-enhancing effect remain unclear. This study is to investigate the role and regulation relation of Akt pathway with downstream kinases of TLR4 receptor in macrophages induced by Astragalus polysaccharide, RAP. The results showed that RAP induced phosphorylation of Akt, NFκB, IRF3 and MAPKs in RAW264.7 cells, and their individual inhibitors not only inhibited their inflammatory factors production and gene expression, but also suppressed the Akt phosphorylation, while Akt inhibitor exerted no effect on MAPKs, NFκB, and IRF3 phosphorylation. Taken together, these results suggested that Akt and IRF3 exerted activation role in RAP induced macrophage, and Akt exerted effect downstream of MyD88 dependent and independent pathway. This study will provide a deeper insight into the signal transduction induced by Astragalus polysaccharides.